Production of adenoviral vectors in 293 cells: a case study of the adaptation of attached cells to grow in suspension - Negrete, Alejandro; Tau, Chuan Ling; Lyddiatt, Andrew (Bentham Science Publishers, 2008)
A study of the production of adenoviral vectors in suspension 293 cells has been explored. A defined serumfree medium (293 SFM II) formulated without human or animal origin components from Invitrogen was used for the suspension adapted 293 cells. It was demonstrated that the 293 cells can be adapted to grow in suspension using serum free medium. The effect of different cell culture parameters was determined. The production technique demonstrated here is expected to simplify purification processes and circumvents the problems associated with serum containing medium.